PENGARUH VARIASI PERENDAMAN UDANG VANAME (Litopenaeus vannamei) DALAM ASAM BUAH ALAMI TERHADAP PENURUNAN KADAR TIMBAL (Pb) DI TAMBAK TRADISIONAL PASIR SAKTI LAMPUNG TIMUR - Susilawati, Devi; sulistiani, widya sartika; widowati, *Hening (BIOLOVA, 2021)
Natural fruit acids are fruits that taste sour containing organic acids, one of which is citric acid, examples of natural fruit acids are tamarind, lime, lemon, pineapple. Natural fruit acids can be used as an ingredient for soaking food derived from fishery products to get rid of the fishy smell and give the people a flavor of cooking. The purpose of this study was to determine the effect of immersion of natural fruit acids on the reduction of lead (Pb) levels in Vanamae shrimp, to determine which immersion variations had the most effect on reducing lead levels in Vanamae shrimp. This study used an experimental method with a completely randomized block design (RAKL). The experiment was carried out with 5 treatments, namely Control (200 grams of shrimp without immersion), Treatment 1 (200 grams of shrimp + 25ml filtrate), Treatment 2 (200 grams of shrimp + 25ml of lime), Treatment 3 (200 grams of shrimp + 25ml filtrate lemon), and treatment 4 (200 grams of shrimp + 25 ml filtrate), each treatment was given 4 times each. Based on the analysis of the anava test, the results obtained Fhit> Fdaf, It was concluded that there was an effect of immersion in natural fruit acids on reducing the levels of lead (Pb) in Vaname shrimp meat, soaking with lime acid was the most significant to reduce the levels of lead metal Pb.